TINGKAT ADOPSI INOVASI SISTEM TANAM JAJAR LEGOWO PADA TANAMAN PADI DI DESA ILOMANGGA KECAMATAN TABONGO KABUPATEN GORONTALO - Nofri Ayinun Hiola; Indriana Indriana (Agropolitan, 2018)
This study aimed to analyze the of farmers adoption level of legowo jajar farming system on rice in the Village Ilomangga Tabongo District Gorontalo. The research method used was census method. The number of respondents in this studied was 30 people. They were the total farmers. The results showed that this study, it could be concluded, that the level of adoption of farmers to the system of planting jajar legowo was in the low category. This showed that the adoption rate of farmers on jajar legowo jajar system had not been maximal, because farmers were less looking for information outside the village and agricultural extension had not worked optimally. Could be suggested too that the farmers were expected to be more proactive in receiving and applying all the information gained for the success of their farms.